Successful Management of Complicated Membranous Nephropathy During Pregnancy. A Report on Two Cases - Nagy, Amro; Zaher, Mohamed (International Journal of Innovative Research in Medical Science, 2025)
Membranous nephropathy (MN) is an uncommon, albeit serious, condition during pregnancy. It is usually associated with adverse maternal and fetal outcomes. Management of MN during pregnancy can require the use of immunosuppressive medications which may be associated with potential adverse effects for both mother and fetus. The scarcity of clear evidence-based guidelines constitutes an additional burden on the caring team. We present two cases of pregnant women without a prior diagnosis of kidney disease, who suffered from nephrotic syndrome and acute kidney injury (AKI) during pregnancy. They received a diagnosis of primary membranous nephropathy (biopsy-proven), were managed with immunosuppressive agents, achieved clinical and laboratory remission using corticosteroids and tacrolimus, and had a favorable pregnancy outcome (live babies). One baby, unfortunately though, died from neonatal sepsis after admission to neonatal intensive care unit (NICU). These cases underscore the complexity of management of glomerular diseases - particularly MN - during pregnancy. The use of dual immunosuppressive drugs was effective in achieving remission but required close patient-, and therapeutic drug level monitoring during pregnancy to avoid drug toxicity. These cases highlight the need for multidisciplinary care and further work to establish evidence-based protocols for such patients, potentially improving outcomes for both mothers and infants.